Surgical treatment of adolescent idiopathic scoliosis: Complications - Al-Mohrej, Omar A. (Ann Med Surg (Lond), 2020)
Despite the fact that spinal surgeries for adolescent idiopathic scoliosis (AIS) result in good outcomes for most patients, they are not without complications either medically or surgically. Neurologic injury represents the most severe complication and is, as such, the most feared. Further complications include dural tears, peripheral neuropathy, surgical-site infections, implant-related issues, thromboembolic events, visual loss, pseudarthrosis, Crankshaft phenomenon, flatback phenomenon, proximal junctional kyphosis, and mortality. It is vital that all spine surgeons to be fully conversant with the possible complications and the proper responses for each of them.